Reporting ChAracteristics of cadaver training and sUrgical studies: The CACTUS guidelines. (May 2022) - Mantica, Guglielmo; Leonardi, Rosario; Diaz, Raquel; Malinaric, Rafaela; Parodi, Stefano; Tappero, Stefano; Paraboschi, Irene; Álvarez-Maestro, Mario; Yuen-Chun Teoh, Jeremy; Garriboli, Massimo; Ortega Polledo, Luis Enrique; Soriero, Domenico; et al.
Abstract: Introduction: Recent systematic reviews highlighted increasing use of cadaveric models in the surgical training, but reports on the characteristics of the models and their impact on training are lacking, as well as standardized recommendations on how to ensure the quality of surgical studies. The aim of our survey was to provide an easy guideline that would improve the quality of the studies involving cadavers for surgical training and research. Methods: After accurate literature review regarding surgical training on cadaveric models, a draft of the CACTUS guidelines involving 10 different items was drawn. Afterwards, the items were improved by questionnaire uploaded and spread to the experts in the field via Google form. The guideline was then reviewed following participants feedback, ergo, items that scored between 7 and 9 on nine-score Likert scale by 70% of respondents, and between 1 and 3 by fewer than 15% of respondents, were included in the proposed guideline, while items that scored between 1 and 3 by 70% of respondents, and between 7 and 9 by 15% or more of respondents were not. The process proceeded with Delphi rounds until the agreement for all items was unanimous. Results: In total, 42 participants agreed to participate and 30 (71.4%) of them completed the Delphi survey. Unanimous agreement was almost always immediate concerning approval and ethical use of cadaver and providing brief outcome statement in terms of satisfaction in the use of the cadaver model through a short questionnaire. Other items were subjected to the minor adjustments. Conclusion: 'CACTUS' is a consensus-based guideline in the area of surgical training, simulation and anatomical studies and we believe that it will provide a useful guide to those writing manuscripts involving human cadavers. Highlights: Standardized guideline on cadaveric model training description. Improved and uniform reporting in human corpses studies. Consensus-based guideline created and edited by multidisciplinary and expert group in the area of surgical training.